Apoptosis of Fas(high) CD4(+) Synovial T Cells by Borrelia-reactive Fas-ligand(high) γδ T Cells in Lyme Arthritis - Vincent, Michael S. (The Rockefeller University Press, 1996)
The function of the minor subset of T lymphocytes bearing the γδ T cell antigen receptor is uncertain. Although some γδ T cells react to microbial products, responsiveness has only rarely been demonstrated toward a bacterial antigen from a naturally occurring human infection. Synovial fluid lymphocytes from patients with Lyme arthritis contain a large proportion of γδ cells that proliferate in response to the causative spirochete, Borrelia burgdorferi. Furthermore, synovial γδ T cell clones express elevated and sustained levels of the ligand for Fas (APO-1, CD95) compared to αβ T cells, and induce apoptosis of Fas(high) CD4(+) synovial lymphocytes. The findings suggest that γδ T cells contribute to defense in human infections, as well as manifest an immunoregulatory function at inflammatory sites by a Fas-dependent process.